Beamforming design for MISO non‐orthogonal multiple access systems. Issue 5 (7th March 2017) - Cui, Jingjing; Ding, Zhiguo; Fan, Pingzhi
Abstract : Non‐orthogonal multiple access (NOMA) is a promising multiple access scheme to enhance the spectrum efficiency of fifth generation networks. In this study, the authors study a downlink multiple‐input single‐output (MISO) system combined with NOMA, where a single beamforming (BF) vector is shared by a group of users. A joint BF and power allocation algorithm is proposed to maximise the sum rate of the users with better channel conditions while guaranteeing the quality of service at the user with poor channel conditions. The formulated problem for sum rate maximisation can be shown as non‐deterministic Polynomial‐time‐hard, and therefore an effective solution based on branch and bound (BB) techniques is proposed. Numerical results are provided to verify that the proposed NOMA‐BF system with the BB algorithm improves the sum capacity significantly compared with the NOMA‐BF system with zero forcing.